The Effect of Morality, Reward, and Psychological Safety on Whistleblowing System with Organizational Support as Moderation: A Survey at PT ABC - Muharom, Ikhsan; Indrabudiman, Amir; Mappadang, Agoestina (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to determine the effect of Reward and Psychological Safety on the Whistleblowing System, with Organizational Support as a moderating variable at PT ABC, Tbk in 2024. The data sampling technique was conducted by distributing questionnaires directly to respondents using the purposive sampling method. The population in this study consisted of 3,537 employees, from which 100 respondents were selected as the research sample. This study employs multiple linear regression analysis and utilizes the SmartPLS statistical software version 3.2.9 as well as Microsoft Excel 2016. The results indicate that the variables of Morality and Reward have a positive effect on the Whistleblowing System, while Psychological Safety has no significant effect. Furthermore, Organizational Support does not moderate the effect of Morality on the Whistleblowing System, but it does moderate the relationship between Reward and Psychological Safety with the Whistleblowing System. These findings suggest that while individual moral values and reward systems are critical drivers of whistleblowing behavior, organizational support mechanisms at PT ABC may not function as intended, potentially reflecting systemic trust deficits or misalignment between formal policies and organizational culture. The study contributes to whistleblowing literature by demonstrating the contextual nature of organizational support in emerging market settings and provides practical implications for designing more effective Whistleblowing Systems in Indonesian corporations.